2022
DOI: 10.38193/ijrcms.2022.4605
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors Affecting Strategy Implementation in Organisations. A Review of Related Literature

Abstract: The failure rate of strategy implementation in both public and private-owned organisations is a cause for concern across the globe. Extant literature reveals that almost 70% of the formulated strategies do not successfully get implemented by organisations for various reasons. Therefore, this paper reviewed literature on psychological factors affecting strategy implementation in organisations. The results of the review revealed employee motivation, commitment, competence, perception and attitudes as the main ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The present results are in line with findings of other researchers who found that the use of psychological factors in management practice improves organizational performance [8], [9], [10].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present results are in line with findings of other researchers who found that the use of psychological factors in management practice improves organizational performance [8], [9], [10].…”
Section: Discussionsupporting
confidence: 93%
“…These motives, as shown by many research data, are crucial to the success or failure of the strategic planning and goal set by an organization [8], [9], [10].…”
Section: Literature Reviewmentioning
confidence: 99%